A Tandem of Rare Complications Due to Stent Infection - Inga Botchorishvili; Vakhtang Kipiani; Rusudan Agladze; Tamar Gaprindashvili; Sergo Khajalia; Zurab Pagava; Levan Vashakidze; Vasil Natsvlishvili (Journal of Clinical Case Reports and Images, 2023)
This report details sequential rare complications arising from a vascular stent infection. Clinical course, microbiology, and imaging are outlined, with emphasis on early recognition and multidisciplinary management. Lessons for device surveillance and antimicrobial stewardship are highlighted.
Keywords: nosocomial infections